Smart companion agent for mental well-being through Deep Learning and NLP - Khan, Rafiur; Sohel, Abdullah Al; Shreyashee, Farhana Azad; Hossain, Shamima; Fiaz, Mahin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.